The diagnostic model of computer system in the form of Petri Net - Krivoulya, G. F.; Laptev, M.; Gharibi, W. (ХАИ, 2008)
The construction of structural computer system model in the form of automatic, limited Petri Net are considered in the article. Proposed model can be used for building diagnosability provision of the computer system. Increasing quantity and complexity of current computer systems (CS) usability leads to necessity of it quality service. Modern computer engineering decides this problem by creating the diagnostic systems and automatic searching for the faults. With usage of them service and repair becomes simpler (1). For modeling the automation diagnostic system of CS necessary to have structure model of CS (2), which permit to define CS transitions from one state to another having different combination of input signals. In this work the structural model of CS in the form of automatic, limited Petri Nets (PN) are proposed.
Keywords: diagnostic model; computer system; reliability; maintainability; durability; failure; correct state; faulty state; operable state